Access control of human resource records: case of the University of Cape Coast, Ghana. (1st July 2021) - Andoh, Raphael Papa Kweku; Attafuah, Alfred
Abstract : Purpose: Security of human resource records is important because of their nature but they are not adequately managed. This study aims to investigate access control issues affecting the security and confidentiality of human resource records at the University of Cape Coast. Design/methodology/approach: A qualitative approach was used to conduct the study. Purposive sampling was used to select staff at the Directorate of Human Resource, University of Cape Coast. A textual analysis was used in analysing responses to open-ended questions leading to the identification of patterns and their subsequent categorisation. An interview was also conducted. Findings: It was found that effective strategies were implemented in controlling access to human resource information and records making them secure. The challenges identified were in two categories: existing and anticipated challenges. Suggestions to resolve the challenges were also enumerated. Originality/value: This study highlights the need to ensure access to human resource records is controlled so that they are secured and kept confidential. This study contributes to knowledge in the broader context of information and records management and specifically, human resource information and records management. It also adds to the dearth of empirical studies that focus on the security and confidentiality of human resource records.